Effect of illness perception on improving asthma symptoms with omega-3 fish oil therapy: Pre-post design - Amelia Lorensia, Mariana Wahyudi, Ananta Yudiarso, Siti Erfina Dwi Kurnia (Journal of Applied Pharmaceutical Science, 2020)
Perception of asthma can affect the patient's self-management and outcome treatment. The outcome is not only determined by symptoms, but also by illness perception. Omega-3 in fish oil has a potential effect on asthma. The study aimed to determine the effect of illness perception on improvement symptoms with fish oil, measured by Asthma-Control-Test (ACT). This research was pre-post test design and purposive sampling, used 1 g daily fish oil then followed-up after 4 weeks, conducted in March 2017–January 2018. The relationship between ACT value and illness perception using chi square test. The study sample consisted of 26 patients. The effectiveness of omega-3 showed that there was significant difference of symptoms after the therapy. It can be concluded there was effect of illness perception relationships related to symptoms. Most of the highest illness perception regarding symptoms and symptoms related to asthma respondents experienced on the individual values, related to symptoms are fixed. While the influence of illness perception on symptoms that got significant results was how long the asthma suffered, and the illness perception on causes of asthma that were significant to changes in asthma symptoms. Omega-3 fish oil was effective in improving asthma symptoms, but the influence of illness perception must also be a concern.
Keywords: Asthma, fish oil, omega-3, asthma symptoms, illness perception.